Foreign assistance and the food crisis of 2007 - 08 - Philip Abbott (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
Dramatically increased international agricultural commodity prices from 2007 to mid-2008 brought food inflation and greater incidence of poverty and malnutrition to developing countries. Higher food prices in 2011 threaten to repeat that crisis. The international community responded strongly to these concerns in 2008 and 2009, promising greater financial support for food aid, safety nets, and agricultural development. The focus of international dialogue differed somewhat from the priorities of national governments, and the objectives of national governments mostly targeting short-run responses to both food security and agriculture prevailed. But a long-run trend of declining foreign assistance to agriculture appears to have reversed. Nevertheless, foreign assistance was small relative to promises made by donors, increased grain and fertilizer import costs, budgetary costs of mitigating policy responses, an investment costs needed to accelerate agricultural production. Both food aid and agricultural development projects have in the past come under the criticisms found in the aid effectiveness debate. Issues to be addressed if renewed efforts toward agricultural development and food aid are to be effective are explored here. High returns to agricultural research require that enabling institutions are developed. National ownership and governance of initiatives that share donor objectives focusing on poverty and long-run development are critical to success.
Keywords: O13; O19; Q11; Q18; 330; foreign assistance; food crisis; agricultural development; food aid; safety nets; aid effectiveness; international commodity prices; Entwicklungshilfe; Landwirtschaftliche Entwicklung; Lebensmittelpreis; Ernährungssicherung